Prediction of the PVTx and VLE properties of natural gases with a general Helmholtz equation of state. Part I: Application to the CH4–C2H6–C3H8–CO2–N2 system. (15th December 2017) - Mao, Shide; Lü, Mengxin; Shi, Zeming
Abstract: A general equation of state (EOS) explicit in Helmholtz free energy has been developed to predict the pressure–volume-temperature-composition ( PVTx ) and vapor-liquid equilibrium (VLE) properties of the CH4 –C2 H6 –C3 H8 –CO2 –N2 fluid mixtures (main components of natural gases). This EOS, which is a function of temperature, density and composition, with four mixing parameters used, is based on the improved EOS of Sun and Ely (2004) for the pure components (CH4, C2 H6, C3 H8, CO2 and N2 ) and contains a simple generalized departure function presented by Lemmon and Jacobsen (1999). Comparison with the experimental data available indicates that the EOS can calculate the PVTx and VLE properties of the CH4 –C2 H6 –C3 H8 –CO2 –N2 fluid mixtures within or close to experimental uncertainties up to 623 K and 1000 bar within full range of composition. Isochores of the CH4 –C2 H6 –C3 H8 –CO2 –N2 system can be directly calculated from this EOS to interpret the corresponding microthermometric and Raman analysis data of fluid inclusions. The general EOS can calculate other thermodynamic properties if the ideal Helmholtz free energy of fluids is combined, and can also be extended to the multi-component natural gases including the secondary alkanes (carbon number above three) and none-alkane components such as H2 S, SO2, O2, CO, Ar and H2 O. This part of work will be finished in the near future.